ANTIBIOTIC PRESCRIPTION TO PEDIATRIC IN HOSPITAL BENGKULU, INDONESIA: ATC/DDD INDEX - Muslim, Zamharira (International Journal of Pharmacy and Pharmaceutical Sciences, 2018)
Objective: The aim of this study was to evaluate the utilization of antibiotics for children in the General Hospital of Dr. M. Yunus Bengkulu, Indonesia by using the ATC/DDD index, which is accepted as a standard method. Methods: This study was descriptive analytic research with qualitative methods. Observations conducted over six months collecting retrospective prescribing data antibiotics in children admitted in January to June 2014. Data obtained assessed antibiotics prescribed in a quantity which is calculated using ATC/DDD index. In this study, DDDs of anti-infective agents are listed for systemic use, according to ATC/DDD 2016 Index. Data pediatric patients hospitalized amounted to 447 patients while fulfilling the inclusion criteria amounted to 103 medical records and the use of antibiotics which recorded 175 prescriptions. Results: The kind of antibiotics that are widely used are gentamicin (34.9%) and ampicillin (34.3%). The highest ACI based group is penicillin group antibiotics (ampicillin) is 26 DDD/100 bed-days. Highest DDDs in this study is ampicillin (101.7). Utilization of antibiotics in hospitals in Bengkulu, Indonesia to pediatric patient higher than suggested by the WHO is based on a quantitative analysis using the ACT/DDD index. Conclusion: Analysis of antibiotic use in children is not rationally quantitatively seen from the total value of ACI in one of the government hospital is very high compared to WHO standard and based on the most antibiotic type was ampicillin followed by gentamicin.